Multistakeholder partnership (MSP) platform for rice in Agusan del Norte, Philippines - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The MSP aims for sustained dissemination to and widespread adoption of ricetechnologies by farmers by embracing a public-private partnership model that brings together various government and non-government organizations in the region representing the different sectors of the rice value chain.